2016
DOI: 10.2214/ajr.15.14896
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy CT–Based Differentiation of Benign Posttreatment Changes From Primary or Recurrent Malignancy of the Head and Neck: Comparison of Spectral Hounsfield Units at 40 and 70 keV and Iodine Concentration

Abstract: DECT-derived spectral Hounsfield units at 40 keV and iodine concentration may be superior to spectral Hounsfield units at 70 keV, which is similar to MDCT, in differentiating benign posttreatment changes from primary or recurrent head and neck malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…7,8,[10][11][12][13][14][15][16][17][18] In the head and neck region, several studies showed iodine concentration (IC) could be useful in CT imaging of cervical lymph nodes or patients with underlying neck malignancy. [19][20][21][22] Until now, a few studies have evaluated IC of thyroid nodules using the DECT data sets to find the malignancy or intranodular hemorrhage; however, they decided the individual CT images for quantification without the detailed topographic knowledge based on ultrasound, which is widely considered as reference imaging modality to assess thyroid nodule. [23][24][25][26] In order to reduce the potential mismatch between the DECT images and other diagnostic methods, representative images of thyroid nodule have to be selected meticulously.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,[10][11][12][13][14][15][16][17][18] In the head and neck region, several studies showed iodine concentration (IC) could be useful in CT imaging of cervical lymph nodes or patients with underlying neck malignancy. [19][20][21][22] Until now, a few studies have evaluated IC of thyroid nodules using the DECT data sets to find the malignancy or intranodular hemorrhage; however, they decided the individual CT images for quantification without the detailed topographic knowledge based on ultrasound, which is widely considered as reference imaging modality to assess thyroid nodule. [23][24][25][26] In order to reduce the potential mismatch between the DECT images and other diagnostic methods, representative images of thyroid nodule have to be selected meticulously.…”
Section: Introductionmentioning
confidence: 99%
“…110 Another study employing fast kV-switching dual-energy technology on 40 patients established that 40 and 70 keV were useful for identifying malignant from benign tissues, also in the head and neck region. 111 Another study using the fast kV-switching dual-energy CT platform on 25 unenhanced head scans revealed that maximal grey matter signal-to-noise ratio, white matter signal-to-noise ratio, and grey matter to white matter contrast-to-noise ratio were obtained using 65 keV virtual monoenergetic images. 112 Optimal posterior fossa image quality was obtained at 75 keV.…”
Section: B3 Creation Of Quantitative Virtual Monoenergetic Imagesmentioning
confidence: 99%
“…VMI and iodine characterization of DECT may play a major role in patients with head and neck cancer in the detection and delineation of the tumor, resulting in more accurate staging [12], equivalent to the perfusion map of perfusion CT of head and neck cancer [13]. It can differentiate normal, inflammatory, and metastatic squamous cell carcinoma cervical lymph nodes based on iodine concentration [14], as well as between benign post-treatment changes from the primary or recurrent head and neck malignancies [15]. Three material differentiation algorithms for identification of iodine and calcium can be used to assess cartilage and bone marrow infiltration, the latter being a new application in head and neck DECT [16].…”
Section: Discussionmentioning
confidence: 99%